2018
DOI: 10.1055/a-0651-7939
|View full text |Cite
|
Sign up to set email alerts
|

Butanol Fraction of Olax Subscorpioidea Produces Antidepressant Effect: Evidence for the Involvement of Monoaminergic Neurotransmission

Abstract: This study sought to investigate involvement of monoaminergic mechanism in the antidepressant action of butanol fraction (BF) of Olax subscorpioidea in rodents and the bioactive principles present. Butanol fraction was evaluated for antidepressant-like effect in the tail suspension, forced swimming and open field tests. All animals were treated with BF (5, 10 & 20 mg/kg) thirty minutes prior to the tests. On the other hand, monoaminergic neurotransmission involvement was probed by pre-treating animals with yoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The results also demonstrated a significant reduction in diarrhoea in the reserpine model of depression [13]. Adeoluwa et al reported the possible involvement of adrenergic, dopaminergic, and serotonergic systems in the antidepressant activity of Olax subscorpioidea [31]. Several antidepressant drugs such as tricyclic antidepressants and monoamine oxidase inhibitors reduce immobility time [46].…”
Section: Antidepressant Activitymentioning
confidence: 84%
See 1 more Smart Citation
“…The results also demonstrated a significant reduction in diarrhoea in the reserpine model of depression [13]. Adeoluwa et al reported the possible involvement of adrenergic, dopaminergic, and serotonergic systems in the antidepressant activity of Olax subscorpioidea [31]. Several antidepressant drugs such as tricyclic antidepressants and monoamine oxidase inhibitors reduce immobility time [46].…”
Section: Antidepressant Activitymentioning
confidence: 84%
“…The butanol leaves' fraction of Olax subscorpioidea revealed rutin, morin, quercetin, and caffeic acid [31]. Oladipupo et al identified the presence of n-hexadecanoic acid (17.6%), 7,10,13-hexadecatrienoic acid, methyl ester (0.84%), 9,17-octadecadienal, (Z)-(2.87%), 9,12-octadecadienoic acid (Z,Z)-(18.0%), octadecanoic acid (4.05%), squalene (4.12%), nonacosane (5.54%), and hentriacontane (1.22%) in the n-hexane leaf extract of the plant [44].…”
Section: Chemical Compounds Isolated and Identified From Olax Subscorpioideamentioning
confidence: 99%
“…and was involved in the monoaminergic mechanism. Analysis of the chemical composition by HPLC indicated caffeic acid as one of the active ingredients of the plant [55]. In another study, ethyl acetate fraction from Tabernaemontana catharinensis A. DC.…”
Section: Antidepressant Activity Of Cinnamic Acidsmentioning
confidence: 93%
“…The main chemical constituents of the plant are alkaloids, steroids, glycosides, saponins, avonoids and terpenoids (Ayandele and Adebiyi, 2007;Victoria et al, 2010). High performance liquid chromatograph (HPLC) analysis of the butanol fraction has revealed the presence of caffeic acid, rutin, morin and quercetin following mapping of peaks with their respective commercial standards (Adeoluwa et al, 2019). In our previous studies, we validated the traditional claim of its analgesic effect (Adeoluwa et al, 2014) and reported an antidepressant property of the crude extract in rodents using despair tests (Adeoluwa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ishola et al (2015) reported anti-in ammatory property of the crude extract of O. subscorpioidea. Furthermore, anti-immobility action and antidepressant effect of the butanol fraction of the leaves in the predictive models of depression were reported and it was concluded that the effect might be mediated via monoaminergic neurotransmission (Adeoluwa et al, 2019). However, with a growing body of evidence linking neuroin ammation and depressive symptoms, there is a need to investigate the potential therapeutic bene t of this plant in in ammatory-related depression.…”
Section: Introductionmentioning
confidence: 99%